Kupffer Cell p38 Mitogen-Activated Protein Kinase Signaling Drives Postburn Hepatic Damage and Pulmonary Inflammation When Alcohol Intoxication Precedes Burn Injury. Issue 10 (October 2016) - Chen, Michael M.; O'Halloran, Eileen B.; Shults, Jill A.; Kovacs, Elizabeth J.
Abstract : Objectives: Clinical and animal studies demonstrate that alcohol intoxication at the time of injury worsens postburn outcome. The purpose of this study was to determine the role and mechanism of Kupffer cell derangement in exacerbating postburn end organ damage in alcohol-exposed mice. Design: Interventional study. Setting: Research Institute. Subjects: Male C57BL/6 mice. Interventions: Alcohol administered 30 minutes before a 15% scald burn injury. Antecedent Kupffer cell depletion with clodronate liposomes (0.5 mg/kg). p38 mitogen-activated protein kinase inhibition via SB203580 (10 mg/kg). Measurements and Main Results: Kupffer cells were isolated 24 hours after injury and analyzed for p38 activity and interleukin-6 production. Intoxicated burned mice demonstrated a two-fold ( p < 0.05) elevation of Kupffer cell p38 activation relative to either insult alone, and this corresponded to a 43% ( p < 0.05) increase in interleukin-6 production. Depletion of Kupffer cells attenuated hepatic damage as seen by decreases of 53% ( p < 0.05) in serum alanine aminotransferase and 74% ( p < 0.05) in hepatic triglycerides, as well as a 77% reduction ( p < 0.05) in serum interleukin-6 levels compared to matched controls. This mitigation of hepatic damage was associated with a 54% decrease ( p < 0.05) in pulmonary neutrophil infiltration and reduced alveolar wall thickening by 45% ( p < 0.05). In vivo p38 inhibition conferred nearly identical hepatic and pulmonary protection after the combined injury as mice depleted of Kupffer cells. Conclusions: Intoxication exacerbates postburn hepatic damage through p38-dependent interleukin-6 production in Kupffer cells.